2018
DOI: 10.1016/j.forpol.2017.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Optimal carbon storage in even- and uneven-aged forestry

Abstract: We study the effects of forest carbon storage on optimal stand management by applying a model where optimal harvests are partial cuttings, implying uneven-aged forestry, or both partial cuttings and clearcuts, implying even-aged forestry. Optimal carbon storage postpones partial cuttings and increases stand volume along the rotation. Carbon pricing may shorten or lengthen the rotation period depending on interest rate and speed of carbon release from wood products. If the carbon price is high, the shadow value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…Earlier economic studies on EM in upland forests considering the externalities caused by GHG emissions are provided by, e.g., van Kooten (1995), Niinimäki et al (2013) and Pihlainen et al (2014). The studies by Pukkala et al (2011), Assmuth et al (2017) and Assmuth and Tahvonen (2018) compared CCF and EM in terms of timber production and carbon sequestration benefits. They concluded that accounting for carbon sequestration benefits will increase the performance of CCF relative to EM.…”
Section: Economic Profitability Of Ccf and Socially Optimal Forest Mamentioning
confidence: 99%
“…Earlier economic studies on EM in upland forests considering the externalities caused by GHG emissions are provided by, e.g., van Kooten (1995), Niinimäki et al (2013) and Pihlainen et al (2014). The studies by Pukkala et al (2011), Assmuth et al (2017) and Assmuth and Tahvonen (2018) compared CCF and EM in terms of timber production and carbon sequestration benefits. They concluded that accounting for carbon sequestration benefits will increase the performance of CCF relative to EM.…”
Section: Economic Profitability Of Ccf and Socially Optimal Forest Mamentioning
confidence: 99%
“…The common result is that increasing carbon price increases optimal stand densities and postpones final felling (e.g., van Kooten et al 1995;Guthrie and Kumareswaran 2009;Daigneault et al 2010;Couture and Reynaud 2011;Pukkala 2011;Raymer et al 2011;Assmuth and Tahvonen 2018). Increasing carbon price increases saw log harvests and decreases pulp wood removals (Pukkala 2011;Assmuth et al 2017) and favors uneven-aged management (Pukkala et al 2011;Assmuth and Tahvonen 2018). Pohjola et al (2018) found that the temporal distribution of the effect of carbon crediting depends on carbon price, low payments having mild but long-lasting impacts.…”
Section: Introductionmentioning
confidence: 99%
“…Since tree breeding has played an integral role in increasing tree growth and productivity [2,3,12], an intriguing question arises: Would landowners gain extra benefits from genetically improved reforestation material in the presence of carbon pricing? Although many studies have addressed the issue of optimal stand management in relation to carbon credits and carbon storage [13][14][15][16], this particular question has drawn little attention so far. Earlier studies in radiata pine [17] and loblolly pine [12] suggested that benefits from carbon sequestration due to tree improvement might be substantial.…”
Section: Introductionmentioning
confidence: 99%